PENGARUH MEDIA PEMBELAJARAN INOVATIF BERBASIS BOTANI TERHADAP KREATIVITAS SISWA PADA MATA PELAJARAN SENI RUPA SISWA KELAS IV SDN 101775 SAMPALI - Windy Antika; Putra Afriadi; Laurensia Masri Perangin-angin; Winara; Try Wahyu Purnomo (STKIP Subang, 2025)
The study aims to determine the effect of Innovative Botanical-Based Learning Media onStudent Creativity in Fine Arts Subjects of Grade IV Students of SDN 101775 Sampali.This type of research is Pre-Experimental (non-design). The sample in this study were 32students of grade IV-A of SDN 101775. Data collection techniques used were observation,interviews, documentation. The research instruments used were observation sheets(person, press, process, product). Data analysis techniques used were normality test,homogeneity test, hypothesis test (T-test). The average post-test value was 74.66.Furthermore, the Paired Sample Test test obtained 0.000 < 0.05 (p < 0.05) then Ho wasrejected and Ha was accepted. So it can be concluded that there is an effect of the use ofbotanical-based learning media on the creativity of students in fine arts subjects of gradeIV SDN 101775 Sampali.